Mammalian derived lipocalin and secretoglobin respiratory allergens strongly bind ligands with potentially immune modulating properties - Janssen-Weets, Bente; Kerff, Frédéric; Swiontek, Kyra; Kler, Stéphanie; Czolk, Rebecca; Revets, Dominique; Kuehn, Annette; Bindslev-Jensen, Carsten; Ollert, Markus; Hilger, Christiane (Frontiers in Allergy, 2022)
Allergens from furry animals frequently cause sensitization and respiratory allergic diseases. Most relevant mammalian respiratory allergens belong either to the protein family of lipocalins or secretoglobins. Their mechanism of sensitization remains largely unresolved. Mammalian lipocalin and secretoglobin allergens are associated with a function in chemical communication that involves abundant secretion into the environment, high stability and the ability to transport small volatile compounds. These properties are likely to contribute concomitantly to their allergenic potential. In this study, we aim to further elucidate the physiological function of lipocalin and secretoglobin allergens and link it to their sensitizing capacity, by analyzing their ligand-binding characteristics. We produced eight major mammalian respiratory allergens from four pet species in E.coli and compared their ligand-binding affinities to forty-nine ligands of different chemical classes by using a fluorescence-quenching assay. Furthermore, we solved the crystal-structure of the major guinea pig allergen Cav p 1, a typical lipocalin. Recombinant lipocalin and secretoglobin allergens are of high thermal stability with melting temperatures ranging from 65 to 90°C and strongly bind ligands with dissociation constants in the low micromolar range, particularly fatty acids, fatty alcohols and the terpene alcohol farnesol, that are associated with potential semiochemical and/or immune-modulating functions. Through the systematic screening of respiratory mammalian lipocalin and secretoglobin allergens with a large panel of potential ligands, we observed that total amino acid composition, as well as cavity shape and volume direct affinities to ligands of different chemical classes. Therefore, we were able to categorize lipocalin allergens over their ligand-binding profile into three sub-groups of a lipocalin clade that is associated with functions in chemical communication, thus strengthening the function of major mammalian respiratory allergens as semiochemical carriers. The promiscuous binding capability of hydrophobic ligands from environmental sources warrants further investigation regarding their impact on a molecule's allergenicity.